Inactivation of Escherichia coli O157:H7 in Dairy Manure Compost with Alkaline Walnut Hull Biochar - Joshua B. Gurtler; Charles A. Mullen (Journal of Food Protection)
Biochar has been used to accelerate heating profiles during composting by increasing oxygenation, which could also reduce microbial pathogens. However, the antimicrobial inactivation of foodborne pathogens in compost, by amending with biochar without increased heating profiles, has not been evaluated. In this study, we examined the ability of biochar to inactivate E. coli O157:H7 (EC) in fresh dairy manure compost by amending with one of four types of biochar. Two slow pyrolysis biochars (high-temperature walnut hull biochar [HTWHB], and walnut hull cyclone biochar [WHCB]), and two fast pyrolysis biochars were examined. Compost with 8.1 log CFU/g of EC + 10% amended biochar was held at 22 °C and analyzed for EC weekly. The control treatment sustained ca. 8.7 log CFU of EC through week 7; however, the bacterium was not detected by direct plating in WHCB compost (below the detection limit) by day 7, through the entire 49 days (which may be attributed to increased compost alkalinity [i.e., pH 10.76]). Populations of EC in compost supplemented with 10% of the three other biochars sustained EC populations ≥9.2 log through the balance of the study. The four biochars were further tested in soil at 17% moisture to determine if concentrations as low as 3.5% could inactivate EC. When 3.5% HTWHB was added to soil, populations were 5.1 log CFU lower than when 10% of the same biochar was amended into dairy compost by week 3. This may indicate that alkaline biochar, amended into lower moisture, soil may be more biocidal than when alkaline biochar is added to high moisture manure compost. The current study demonstrates that highly alkaline walnut hull cyclone biochar is capable of reducing up to 8 log of EC in high moisture fresh compost in only 7 days, while as little as 3.5% alkaline WHCB in 17% moisture soil can reduce 6.7 log of EC in only 14 days. These results may assist farmers in amending compost, manure, cattle feedlots, or soil with biochar to reduce EC, and potentially other pathogens (e.g., Salmonella enterica, Campylobacter jejuni, and Listeria monocytogenes), with the goal of reducing the dissemination of human bacterial pathogens to meat, poultry, and fresh produce.